Giant Intrathoracic Left-Sided Vagal Schwannoma - Kirschbaum, Andreas; Ritz, Rainer; Pehl, Anika; Bartsch, Detlef (The Thoracic and Cardiovascular Surgeon Reports, 2013)
Extensive intrathoracic tumors are rarely diagnosed radiologically without pre-existing symptoms. If located in the posterior mediastinum, it is most probably a neurogenic tumor. Schwannoma is the most frequent neurogenic neoplasia in this location, and most schwannomas are benign. To specify the diagnosis, a thoracic computed tomography must be done; if the growth is close to the medullary canal, a magnetic resonance tomography of the spinal column is necessary to detect neuroforamen infiltration. Our surgical goal was complete excision of the tumor, although many authors favor a minimally invasive approach. In our patient we performed open, en bloc removal of the tumor; removal of parts of the intraforamen was also necessary, which necessitated revision of the affected neuroforamen. Histologically this was a very rare case of vagal schwannoma (which has an incidence of less than 6% of all neurogenic tumors). This patient has a very promising prognosis following complete tumor resection.
Keywords: chest wall; mediastinal tumor; lung; benign or congenital lesions